2021
DOI: 10.1016/j.ajog.2021.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use and ovarian cancer risk for BRCA1/2 mutation carriers: an international cohort study

Abstract: and International BRCA1/2 Carrier Cohort Study BACKGROUND: Ovarian cancer risk in BRCA1 and BRCA2 mutation carriers has been shown to decrease with longer duration of oral contraceptive use. Although the effects of using oral contraceptives in the general population are well established (approximately 50% risk reduction in ovarian cancer), the estimated risk reduction in mutation carriers is much less precise because of potential bias and small sample sizes. In addition, only a few studies on oral contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…Collectively, these data demonstrate that oral contraceptives reduce the risk of ovarian cancer by 45% to 50% in carriers of a BRCA1 mutation and 50% in carriers of a BRCA2 mutation 236,238,239 .…”
Section: Evidence In High-risk Populationsmentioning
confidence: 76%
See 3 more Smart Citations
“…Collectively, these data demonstrate that oral contraceptives reduce the risk of ovarian cancer by 45% to 50% in carriers of a BRCA1 mutation and 50% in carriers of a BRCA2 mutation 236,238,239 .…”
Section: Evidence In High-risk Populationsmentioning
confidence: 76%
“…In a recent meta-analysis of six studies conducted among women with a BRCA1 or BRCA2 mutation, Moorman et al reported that a history of oral contraceptive use was associated with a 42% reduction in risk (OR = 0.58; 95% CI 0.46-0.73) in women with either mutation, consistent with risk estimates observed in the general population 237 . Moreover, this protective effect appears to increase with long-term use and persists over 20 years after discontinuation of use 238 .…”
Section: Evidence In High-risk Populationsmentioning
confidence: 97%
See 2 more Smart Citations
“…La duración media del uso fue de 7 años para las portadoras de BRCA1 y BRCA2 que desarrollaron cáncer de ovario y de 9 y 8 años para las portadoras no afectadas de BRCA1 y BRCA2 con cáncer de ovario, respectivamente. En el caso de las portadoras de la mutación BRCA1, una mayor duración del uso de anticonceptivos orales se ha asociado con mayor reducción del riesgo de cáncer de ovario, y la protección es a largo plazo(64) .…”
unclassified